Long‐Term Follow‐Up of Multilevel Thoracic Ossification of the Posterior Longitudinal Ligament Following Circumferential Decompression via Posterior Approach: A Retrospective Study - Xiao Liu; Shu‐heng Zhai; Qing‐peng Song; Feng Wei; Liang Jiang; Chui‐guo Sun; Xiao‐guang Liu; Wei‐shi Li (Orthopaedic Surgery, 2022)
Objective To examine the postoperative progression of multilevel thoracic posterior longitudinal ligament (OPLL) at circumferential decompression (CD) levels and evaluate the long‐term results after CD via the posterior approach. Methods Clinical data from 16 patients with thoracic myelopathy secondary to OPLL who underwent CD at a single center were evaluated retrospectively from 2007 to 2014 and were followed up for more than 60 months. Patients of all sexes and ages were included in the study. Thin‐slice computed tomography scans obtained at the time of surgery and the most recent follow‐up were analyzed. The ossified area was measured on the axial reconstructed scan of the most obvious protrusion of ossification at the CD level. The neurological outcomes were evaluated using modified Japanese Orthopaedic Association (JOA) scores and Hirabayashi recovery rates (HRRs). Continuous variables were presented as the mean ± standard deviation and were analyzed using the Student's t‐test, while categorical variables were tested using Fisher's exact test. Results Among all patients, the most predominant type was the mixed type (9/16, 56.3%), while the circumscribed type was only found in two patients (12.5%), and the continuous type was found in five patients (31.2%). Six cases were associated with ossification of the ligamentum flavum, and two cases were combined with cervical OPLL. The OPLL area at the CD level increased in all patients. The mean follow‐up period was 5.5 ± 0.92 years (range 5–8 years). The mean area of ossification increased from 35.63 ± 39.23 mm2 at the time of surgery to 99.94 ± 65.39 mm2 at the last follow‐up visit (P < 0.01). There was no internal fixation disorder on any computed tomography scan after the operation. The average JOA score of all patients improved from 4.2 ± 2.2 points before surgery to 8.4 ± 2.6 points at the final follow‐up (P < 0.01). The overall HRR was 61.8%. None of the patients exhibited any neurological deterioration due to OPLL progression. One patient developed a severe gait disturbance due to worsening lumbar canal stenosis, an unrelated cause, but the other 15 experienced gait disturbance improvements. Conclusions According to the long‐term follow‐up results, although OPLL progression did not decrease or stop after removing the OPLL mass, CD is a safe and effective procedure that can provide adequate reserve ventral space to cope with postoperative OPLL progression.